Biomarkers of oxidative stress and its nexus with haemoglobin variants and adverse foeto-maternal outcome among women with preeclampsia in a Ghanaian population: A multi-centre prospective study - Abdul, Ganiwu; Osei-Wusu, William; Asare, Gordon Akuffo; Daud, Samira; Opoku, Stephen; Tamakloe, Valentine Christian Kodzo Tsatsu; Frimpong, Joseph; Sackey, Benedict; Boadu, Wina Ivy Ofori; Paintsil, Vivian; Annani-Akollor, Max Efui; Wiafe, Yaw Amo; et al. (PLOS ONE, 2023)
Introduction Haemoglobin variants and preeclampsia (PE) are associated with adverse fatal events of which oxidative stress may be an underlying factor. Oxidative stress (OS) among preeclamptic women with haemoglobin variants has been well established. It is, however, unclear whether haemoglobin variants induce OS to aggravate the risk of adverse foeto-maternal outcomes in pregnant women with preeclampsia. We measured the levels of OS biomarkers and determined the association between haemoglobin variants, and adverse foeto-maternal outcomes among pregnant women with PE. Methods This multi-centre prospective study recruited 150 PE women from three major health facilities in both Bono and Bono east regions of Ghana from April to December 2019. Haemoglobin variants; HbAS, HbSS, HbSC, HbCC, and HbAC were determined by haemoglobin electrophoresis. OS biomarkers such as malondialdehyde (MDA), catalase (CAT), vitamin C, and uric acid (UA) along with haematological and biochemical parameters were estimated using standard protocol. Adverse pregnancy complications (APCs) such as post-partum haemorrhage (PPH), HELLP (Haemolysis, Elevated liver enzymes, Low platelet count) syndrome, preterm delivery, neonatal intensive care unit (NICU) admission, and neonatal jaundice were recorded. Results Of the 150 pregnant women with preeclampsia, the distribution of haemoglobin AA, AS, AC, CC, SS and SC phenotypes were 66.0%, 13.3%, 12.7%, 3.3%, 3.3% and 1.3%, respectively. The most prevalent foeto-maternal outcomes among PE women were NICU admission (32.0%) followed by PPH (24.0%), preterm delivery (21.3%), HELLP syndrome (18.7%), and neonatal jaundice (18.0%). Except for vitamin C level which was significantly higher in patients with at least a copy of Haemoglobin S variant than those with at least a copy of Haemoglobin C variant (5.52 vs 4.55; p = 0.014), levels of MDA, CAT, and UA were not statistically significantly different across the various haemoglobin variants. Multivariate logistic regression model showed that participants with HbAS, HbAC, having at least a copy of S or C and participants with HbCC, SC, SS had significantly higher odds of neonatal jaundice, NICU admission, PPH and HELLP syndrome compared to participants with HbAA. Conclusion Reduced levels of vitamin C are common among preeclamptics with at least one copy of the HbC variant. Haemoglobin variants in preeclampsia contribute to adverse foeto-maternal outcomes with Haemoglobin S variants being the most influencing factor for PPH, HELLP, preterm labour, NICU admission, and neonatal jaundice.